Impact of geopolitical risk on firm financial fragility: International evidence from listed companies - Hüseyin Kaya; Yasir Küçükşahin; Mücahit Çitil (Borsa Istanbul Review)
In this study, we investigate the impact of geopolitical risks on financial fragility of firms across 40 countries in the period from 1990 to 2022. The Altman Z-Score is used as an indicator of financial fragility, while the Geopolitical Risk Index is employed as a measure of geopolitical risk. The analysis includes firm-specific indicators and macroeconomic factors from a novel panel dataset. We use panel fixed-effect estimation method and employ system GMM for robustness check. We also examine the relationship according to three different income level groups of countries. The results reveal that geopolitical risks significantly increase the financial fragility of firms, and this effect is stronger in upper middle-income countries. Along with macroeconomic environment and firm characteristics, firms’ heightened sensitivity to geopolitical instability emphasizes the essential role of geopolitical stability in maintaining firm financial health.